Models of care: the influence of nurse communication on patient safety. - Anthony MK; Preuss G (Nursing Economic$)
The authors explore the communication role of nurses with respect to the nature of clinical information, environmental variables, communication behaviors, current labor and safety issues, and the effects of delivery models and technology.The dangers inherent in the transmission of information are discussed in terms of the decay and uncertain saliency of information leading to information funneling and ultimately failure to rescue.Factors influencing the sharing of information include the availability of information affecting the likelihood of sharing and the continuity and cohesiveness of work groups.The complexity of the patient and work environment have placed a burden on the nurse's cognitive ability to attend to and recall information.Technology applications have provided mechanisms for prompting and safeguarding information while increasing access to information.Nursing leaders are key to structuring the care environment as well as managing the performance of and resources for systems of communication that enable patient rescue and safety.